THE EFFECT OF HEDONIC LIFESTYLE ON THE CONSUMPTION BEHAVIOR OF ACCOUNTING STUDENTS AT UNIVERSITAS NEGERI SURABAYA - Johanto, Ihsanul; Anwar, Muhammad Reza Pahlevi (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to analyze the effect of hedonic lifestyle on the consumption behavior of accounting students at Surabaya State University. Hedonic lifestyle refers to individual preferences that tend to seek pleasure, enjoyment, and comfort excessively in daily life, which has an impact on purchasing decisions and consumption behavior. Accounting students as research subjects were chosen because they are in the transition phase between academic life and professional life, which is often characterized by social pressure and the desire to follow growing consumption trends. This research uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to accounting students at Surabaya State University. The number of respondents was 100 students selected using purposive sampling technique. Data analysis was conducted using multiple linear regression to examine the relationship between the independent variable, hedonic lifestyle, and the dependent variable, consumption behavior. The results showed that a hedonic lifestyle has a significant influence on student consumption behavior. Students with a more hedonic lifestyle tend to spend money on goods and services that are considered capable of providing pleasure or social status, without considering actual needs. In addition, factors such as peer influence, social media, and the urge to follow trends were also found to reinforce this hedonic consumption behavior. This study also found that hedonic consumption behavior can negatively impact students' ability to manage personal finances, which in turn can affect the quality of their academic life and psychological well-being. Therefore, it is important for educational institutions to provide understanding and education on good financial management as well as the negative impact of consumptive lifestyles. The findings contribute to the literature on consumption behavior among university students, particularly in the context of hedonic lifestyle and its implications on students' financial and academic well-being. In addition, this study also opens up opportunities for further research on strategies that can be used by university students in coping with the increasing pressure of a hedonistic lifestyle. Thus, this study emphasizes the need for awareness of the influence of hedonic lifestyles on student consumption behavior and the importance of more structured interventions in shaping more rational and sustainable consumption behavior among accounting students.